Phase 1 Trials in Pancreatic Cancer - Yu, Esther; Saif, Muhammad Wasif; Huber, Kathryn (JOP. Journal of the Pancreas, 2014)
Despite many clinical trials over the last two decades since the approval of gemcitabine, the survival of patients with pancreatic cancer has improved by a few only months. This disappointing reality underlines an urgent need to develop more effective drugs or better combinations. A variety of phase I trials were presented at the annual meeting of ASCO 2014 focusing on locally advanced and metastatic pancreatic cancer. We summarize four abstracts (abstracts #4116, #4123, #4026, #4138). Image: Radiation Oncology, Tufts Medical Center. Boston, MA, USA.